A 16-Year-Old Male with Thoracic Compression following Posterior Spinal Instrumentation and Fusion for Marfan-Associated Syndromic Scoliosis - Mason Uvodich; Ross Barman; Adam Reitz; Matthew Sexton (Case Reports in Orthopedics)
Introduction. Marfan syndrome is an autosomal dominant disorder caused by a mutation in the FBN1 gene which affects connective tissue. The features of Marfan syndrome include many musculoskeletal abnormalities which require orthopaedic surgical intervention. Given the expansive phenotypic variations and comorbidities associated with Marfan syndrome, knowledge of perioperative risk factors and potential complications is essential. Case. In this case report, the authors describe a patient with Marfan syndrome who underwent spinal instrumentation and fusion from T3 to L4 for correction of syndromic scoliosis. The patient had a complicated perioperative course requiring significant fluid resuscitation and vasoactive medications to support blood pressure. He required intensive care unit level care for continued hemodynamic instability despite resuscitation in the postoperative period. Common causes of postoperative hypotension such as hypovolemic shock, sepsis, ongoing hemorrhage, and prolonged effects of anesthesia were diagnostically ruled out. Ultimately, the patient’s refractory hypotension was determined to be from mechanical compression, both from prolonged intraoperative prone positioning exacerbated by pectus excavatum and from the surgically corrected spine decreasing the diameter of his thoracic cavity (as referenced by his postoperative Haller index). Conclusion. Mechanical compression of thoracic contents as a result of a worsening chest wall deformity can be a complication of spinal deformity correction.